Dr. Jordan Rihani — Deep Plane Facelift — Fort Worth - Rihani, Jordan (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Jordan Rihani, practicing in Fort Worth, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003161; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; fort worth